Neuroendocrine tumors of the gastrointestinal tract and the role of cytotoxic chemotherapy. Issue 4 (2nd April 2016) - Khasraw, Mustafa; Ananda, Sumitra; Michael, Michael
ABSTRACT: Neuroendocrine tumors (NETs) comprise a heterogeneous group of tumors derived from peptide- and amine-secreting cells of the neuroendocrine system. NETs commonly arise in the gastrointestinal tract but can arise in most organs of the body. Although the incidence of NETs is not high, the prevalence is relatively high because many patients may live relatively long periods without major symptoms from the disease. Whilst many of these tumors take on an indolent clinical course, they constitute a therapeutic challenge when they progress, metastasize and become symptomatic. Treatment requires a multidisciplinary approach that may include cytotoxic chemotherapy. Almost all clinical trials investigating cytotoxic chemotherapy in NETs are small single-arm studies, hence guidelines are derived from expert opinion and from extrapolating results from small-cell lung cancer studies. This article provides a broad coverage of systemic therapies for NETs but focusses on the role of cytotoxic chemotherapy.